1945
DOI: 10.1021/ja01226a036
|View full text |Cite
|
Sign up to set email alerts
|

The Occurrence of the Growth Factor Strepogenin in Purified Proteins1

Abstract: The bacterial growth factor, tentatively called strepogenin, which stimulates the growth of a variety of bacteria, has been found in partial hydrolysates of vitamin-free casein.* It has therefore seemed advisable to examine several purified proteins for their ability to yield the factor on partial hydrolysis. Since Wright and Skeggsb have reported strepogenin-like activity for enzymic digests of casein, we have tested such preparations and found them to be more active than the partial hydrolysates prepared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

1946
1946
1975
1975

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(21 citation statements)
references
References 2 publications
1
20
0
Order By: Relevance
“…The inhibitor utilized in the present study was prepared from fresh beef liver and after ashing it was ineffective in vitro. The identity of insulinase-inhibitor remains unknown other than it is a peptide (or peptides) of low molecular weight which is resistant to hyd'rolysis by acid, trypsin and pepsin and which resembles strepogenin (9) in a number of characteristics.…”
Section: Effect Of 'Insulinase-inhibitor' On Destruction Of Insulin Bymentioning
confidence: 99%
“…The inhibitor utilized in the present study was prepared from fresh beef liver and after ashing it was ineffective in vitro. The identity of insulinase-inhibitor remains unknown other than it is a peptide (or peptides) of low molecular weight which is resistant to hyd'rolysis by acid, trypsin and pepsin and which resembles strepogenin (9) in a number of characteristics.…”
Section: Effect Of 'Insulinase-inhibitor' On Destruction Of Insulin Bymentioning
confidence: 99%
“…Sprince & Woolley (1945) have shown that a substance of this nature, strepogenin, is required for the growth of certain lactic bacteria. No preparation of strepogenin was available for testing, but the partial tryptic casein digests were prepared so as to conserve this material as much as possible (Dr Woolley, personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…It is unlikely that this factor is strepogenin, because Sprince and Woolley (1945) showed that strepogenin is present in commercial casein. It probably is not any of the factors which recently has been shown to be related to or identical with folic acid (Peterson, 1946).…”
Section: Discussionmentioning
confidence: 99%